KONTRIBUSI PENDAPATAN NELAYAN TERHADAP PENDIDIKAN ANAK DI DESA LERO KECAMATAN KABUPATEN DONGGALA - Rifaldin, Moh.; Utomo, Lilik Prihadi; Suyuti, Suyuti (Katalogis, 2020)
This study aims to analyze (1) the level of income of fishermen in Lero Village and Lero Tatari Village, Sindue District, Donggala Regency and (2) the contribution of fishermen's income to children's education in Lero Village Sindue District, Donggala Regency. This type of research is quantitative research. Data collection techniques are observation, questionnaire and in-depth documentation with the results of the study. The data analysis technique is descriptive and quantitative using the SPSS Version 16. Statistical program The results of this study are that the income level of fishermen in Lero Village shows a low income level of 29.3%, at a moderate income level of 46.3%, at a high income level of 14.6% and at a very high income level of 9.8%. The level of education of children at the elementary level is 41.2%, the level of education of children at junior high school level is 16.3%, the level of education of children at the high school level is 29.1%, and the level of education of children at tertiary level is 10.5%. The contribution of fishermen's income to children's education in the village of Lero obtained X ^ 2 tables of 16.919 and X2 2 counts for 70,960 and was determined using the contribution formula (X2 2 count-X ^ 2 table) X 100% (Contribution = 70,960-16,919 = 54,041 X 100% = 54,041%). Fishermen's income contributes to children's education by 54.041%, the remaining 45.959%.